3nLcn2, a teleost lipocalin 2 that possesses antimicrobial activity and inhibits bacterial infection in triploid crucian carp. Issue 102 (July 2020) - Zhou, Zejun; Feng, Chen; Liu, Xiaofeng; Liu, Shaojun
Abstract: Lipocalin 2 (Lcn2) has been identified in mammals, however, the in vivo function of fish Lcn2 is essentially unknown. Triploid crucian carp (3n = 150) of red crucian carp (female, 2n = 100) and allotetraploid (male, 4n = 200) shows better resistance to pathogenic infections. To elucidate the antimicrobial mechanism of triploid crucian carp, we examined the function of a novel Lcn2 from triploid crucian carp (3nLcn2). 3nLcn2 is 183 residues in length and contains a conserved lipocalin domain. Quantitative real time reverse transcription PCR (qRT-PCR) analysis showed that 3nLcn2 expression occurred in multiple tissues and was upregulated by bacterial infection in a time-dependent manner. We found that purified recombinant 3nLcn2 (r3nLcn2) exerted bactericidal activity to Aeromonas hydrophila and Escherichia coli. qRT-PCR detected increased expression of pro-inflammatory cytokines and tight junctions in fish with 3nLcn2 overexpression. Fish administered with 3nLcn2 exhibited enhanced intestinal barrier and resistance against bacterial infection. These results provide the first evidence that 3nLcn2 is a functional lipocalin with antimicrobial activity and plays a positive role in the immune defense during bacterial infection. Highlights: mRNA expression of 3nLcn2 was significantly induced by bacterial challenge. 3nLcn2 exhibited bactericidal activity to Aeromonas hydrophila and Escherichia coli. 3nLcn2 could increase the expression of pro-inflammatory cytokines and tight junctions. 3nLcn2 could enhance intestinal barrier and resistance against bacterial infection.